Development of STEM-Nuanced Mathematics Teaching Materials to Enhance Critical Thinking in the Challenge Based Learning Model - Listiani, Devi Ayu; Kurniasih, Ary Woro (Universitas Negeri Semarang, 2025)
This research aims to develop STEM-based mathematics teaching materials in the Challenge-Based Learning model to enhance students' critical thinking. This research used the Research and Development method with the 4D model, but up to the development stage. The research was conducted at SMP Negeri 3 Karanganyar. The data collection techniques used were interviews, tests, and questionnaires. The purpose of this research is to produce a product that meets the feasibility, readability, effectiveness, and positive student response. The results showed that the average percentage of feasibility of the mathematics teaching materials developed was 91.34% which is very feasible. The results of the readability test, obtained Q = 6.0967, show teaching materials that are easy for students to understand. The mathematics teaching materials developed are effective in improving students' critical thinking skills because they meet the five research hypotheses. The average score of students' responses to the developed teaching materials is a very good criterion. Based on the results of the research, STEM-nuanced mathematics teaching material products were obtained to improve critical thinking in 94% the Challenge-Based Learning model, which is feasible, easy to understand, effective in improving students' critical thinking skills, and received a very good response. Similar research can be done by applying learning styles in depth and maximizing the use of Padlet media to be active in discussions to hone analysis and inference skills.